2001
DOI: 10.1111/1468-2397.00163
|View full text |Cite
|
Sign up to set email alerts
|

The Videotaped Addiction Challenge Tool: a new instrument for qualitative substance abuse assessment, treatment planning and research in therapeutic communities

Abstract: This article describes the different phases of the development and implementation of the Videotaped Addiction Challenge Tool (VACT, initially termed the Video Addiction Challenge Test). This instrument employs a video depicting the `average life‐story' of a resident of a Therapeutic Community for substance abusers. The video film is used as a clinical method for assessment and individual treatment planning, and as a research instrument that gives care‐givers a deeper insight into the residents' personal charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
0
13
1
3
Order By: Relevance
“…19 Innovative techniques such as videotaping for assessment and individual treatment planning may also be of help. 20 Notwithstanding, in the present study, we found that almost half of the surviving group did attain working status or were engaged in vocationally oriented schooling either with or without the help of methadone maintenance treatment. Methadone maintenance treatment has not been a possibility for more than 5 years in Norway.…”
Section: Discussioncontrasting
confidence: 47%
“…19 Innovative techniques such as videotaping for assessment and individual treatment planning may also be of help. 20 Notwithstanding, in the present study, we found that almost half of the surviving group did attain working status or were engaged in vocationally oriented schooling either with or without the help of methadone maintenance treatment. Methadone maintenance treatment has not been a possibility for more than 5 years in Norway.…”
Section: Discussioncontrasting
confidence: 47%
“…New interesting instruments (Bio-MAPS, VACT) and models (SAFE), as well as a (still growing) European database were developed. The initial results of the project are recently published and seem to be promising [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Another European TC research focusing on client profi les was a study by Broekaert and Soyez [22] . They developed the Video Addiction Challenge Tool (VACT), an instrument employing a video depicting the 'average lifestory' of a client in a Belgian TC.…”
Section: Tc Research In Europe: Focus On Client Profi Lesmentioning
confidence: 99%
“…The whole was coordinated by the Maastricht University in the Netherlands in close collaboration with the Ghent University in Belgium. Results of the IPTRP project have been published in several articles [1,21,22,[26][27][28][29][30][31] .…”
Section: Data Collection and Study Samplementioning
confidence: 99%